Análise comparativa da proliferação celular entre carcinomas de células escamosas orais HPV-positivos e HPV-negativos Comparative analysis of the cellular proliferation between HPV-positive and HPV-negative oral squamous cell carcinomas - Danielle Albuquerque Pires Rocha; Lélia Batista de Souza; Leão Pereira Pinto (Sociedade Brasileira de Patologia Clínica, 2007)
INTRODUÇÃO: O carcinoma de células escamosas oral (OSCC) representa a neoplasia maligna mais freqüente em boca, e, entre os agentes etiológicos implicados, o papilomavírus humano (HPV) tem sido extensivamente estudado nos últimos anos. OBJETIVO: Analisar comparativamente os índices de proliferação celular em OSCCs HPV-negativos e HPV-positivos. MATERIAL E MÉTODO: A amostra consistiu em 11 casos de OSCCs HPV-positivos (10 infectados por HPV-18 e um por HPV-16 e 18) e 13 HPV-negativos, previamente analisados quanto à presença ou ausência, bem quanto à tipagem viral por proteína C reativa (PCR) (primers GP5+/GP6+) e hibridização dot blot, respectivamente. No método imunoistoquímico utilizou-se a técnica da estreptoavidina-biotina, com anticorpo para a proteína nuclear Ki-67. RESULTADOS: O teste estatístico não-paramétrico de Mann-Whitney revelou que não houve diferença estatisticamente significativa entre os grupos HPV-positivo e HPV-negativo (p = 0,72). Discussão: Os estudos semelhantes a estes são poucos e não são concordantes em demonstrar maior atividade proliferativa tumoral nos casos HPV-positivos em relação aos HPV-negativos, seja através da análise da expressão de proteínas relacionadas ao ciclo celular, seja na análise direta da fração proliferativa tumoral. CONCLUSÃO: Não houve diferença no índice de proliferação celular entre os grupos de OSCCs HPV-positivo e HPV-negativos. BACKGROUND: Oral Squamous Cell Carcinoma (OSCC) is the most common malignant tumor in the mouth, and the human papillomavirus (HPV) has been hardly studied as a possible etiologic agent. OBJECTIVES: The aim of this study was to compare the rates of cell proliferation in HPV-positive and HPV-negative OSCC, using the immunohistochemical antibody Ki-67. MATERIAL AND METHOD: The sample consisted of 11 cases HPV-positive OSCC (10 cases infected with HPV-18 and 1 case infected with HPV-16 and 18) and 13 cases HPV-negative OSCCs, previously analyzed regarding the presence or absence of HPV, as well as the viral type, using PCR (primers GP5+/GP6+) and dot blot hybridization, respectively. Immunohistochemical study was performed by streptoavidin-biotin technique with antibody against nuclear protein Ki-67. RESULTS: The mean of positivity index of the HPV-positive OSCC (17.7%) was greater than HPV-negative OSCC (14.2%), however the statistic analysis showed that standard deviation in both groups was very high, almost equal the mean (14% and 9.5%, respectively). The Mann-Whitney non-parametric statistic test disclosed that there wasn't a significantly statistical difference between the groups. DISCUSSION: Similar studies to these are few and they are not concordant in demonstrating a bigger tumoral proliferative activity in those cases infected by HPV in relation to those not infected, either through the analysis of the protein expression related to the cellular cycle as in the direct analysis of the tumoral proliferative fraction. CONCLUSION: There were not differences in the rates of cell proliferation between the HPV-positive and HPV-negative grups.